Logistics Service Quality, Logistics Cost, and Customs Clearance on Delivery Service Loyalty in the Indonesian Holtikura Industry - Nofrisel Nofrisel; Tiya Gusti Karina; Siti Maemunah; Sri Raharjo; Euis Saribanon (Dinasti Publisher, 2024)
Abstract: Horticultural companies in Indonesia have links with shipping service companies. Relationships to support vegetable production activities that will be marketed to various places. Problems often experienced by horticultural companies are delays in delivery to the destination, price of goods, quality of logistics services, logistics costs, custom clearance, satisfaction of horticultural companies, and loyalty of delivery services. This research method is a quantitative method with data processing using the Structural Equation Modeling (SEM) method, namely Partial Least Square (PLS)-SEM. The research results of the Logistic Service Quality, Logistic Cost and Custom Clearance variables have a direct effect on Horticultural Company Satisfaction. Logistic Service Quality and Custom Clearance have a positive influence on delivery service loyalty, while Logistic Cost and Horticultural Company Satisfaction do not have a positive influence on delivery service loyalty. It is hoped that further research will not only focus on Indonesia but can be developed to developing or developed countries. Keyword: quality of logistics services, logistics costs, custom clearance, horticultural companies, satisfaction with shipping service loyalty